The Relationship between Body Mass Index and Risk of Failure following Meniscus Repair - Sommerfeldt, Mark F.; Magnussen, Robert A.; Randall, Kyle L.; Tompkins, Marc; Perkins, Bryan; Sharma, Avijit; Blackwell, Ryan; Flanigan, David C. (The Journal of Knee Surgery, 2016)
It is unknown whether body mass index (BMI) influences outcomes of meniscus repair. We hypothesized that increased BMI would be associated with increased risk of failure. A retrospective study was performed involving patients who had undergone meniscus repair between 2008 and 2012. Chart review and phone interviews were conducted to determine which patients required additional surgery. Patients were categorized as normal BMI (<25) or increased BMI (≥25). Of the 305 patients who met study criteria, 216 (70.8%) were available for follow-up at a mean of 19 months postoperatively. A total of 100 patients (46.3%) had a BMI <25 and 116 (53.7%) patients had a BMI ≥25. BMI was less than 35 in 90% of patients. Thirty-four patients (15.7%) required further surgery for a repair failure. Failure occurred in 20 patients (20%) in the normal BMI group and 14 patients (12%) in the increased BMI group (p = 0.14). Logistic regression revealed a trend toward decreased odds of repair failure in the increased BMI group (odds ratio: 0.46; 95% confidence interval: 0.20–1.05; p = 0.065). Patients with a BMI ≥25 did not have a higher risk of meniscus repair failure relative to those with a BMI <25. Given these findings, surgeons should not consider moderately increased BMI as a contraindication to meniscal repair. The effect of BMI greater than 35 on outcomes of meniscal repair remains unclear and warrants further study.
Keywords: body mass index; meniscus repair; cohort study